Trimethylamine N-Oxide Exacerbates Cardiac Fibrosis via Activating the NLRP3 Inflammasome - Li, Xueling; Geng, Jin; Zhao, Jinxuan; Ni, Qianqian; Zhao, Chenze; Zheng, Yaru; Chen, Xiaomin; Wang, Lihong (Frontiers in Physiology, 2019)
Background/Aims: Gut microbiota has been reported to correlate with a higher mortality and worse prognosis of cardiovascular diseases. Trimethylamine N-oxide (TMAO) is a gut microbiota-dependent metabolite of specific dietary nutrients, which is linked to cardiac fibrosis. Recent reports have suggested that the activation of Nucleotide-binding oligomerization domain (NOD)-like receptor protein 3 (NLRP3) inflammasome contributed to cardiac fibrosis. However, whether TMAO mediates cardiac fibrosis via activating NLRP3 inflammasome remains unclear. Methods and Results: To determine the role of TMAO–mediated cardiac fibrosis, we established mouse models of doxorubicin (DOX)-induced cardiac fibrosis with or without TMAO in drinking water. TMAO exacerbated DOX-induced cardiac dysfunction, heart weight and cardiac fibrosis manifested by enhanced collagen accumulation, higher profibrotic levels and elevated inflammatory factors as well as NLRP3 inflammasome activation. Using primary cultured mouse cardiac fibroblast, our results indicated that TMAO promoted proliferation, migration and collagen secretion in a dose-dependent manner by TGF-β/Smad3 signaling. Furthermore, TMAO treatment induced NLRP3 inflammasome activation including oxidative stress in cultured cardiac fibroblast. Importantly, the silencing of NLRP3 presented a protection effect against cardiac fibrosis including cellular proliferation, migration and collagen deposition in vitro. Conclusion: Our data suggested that TMAO aggravated DOX-induced mouse cardiac fibrosis, at least in part, through activation of the NLRP3 inflammasome, providing a new potential target for preventing the progression of cardiac fibrosis.